A Igreja católica, a política e a sociedadade - Alonso, Aurelio (Estudos Avançados, 2011)
This essay aims to analyze the relations between the Catholic Church and the Cuban socialist State over the years after the Revolution. To this end, we established a chronology of these relations that includes the ensuing frictions, conflicts and dialogues - from the expulsion of a bishop and his deportation to Spain after a procession dedicated to Our Virgin of Charity [La Virgen de la Caridad del Cobre, Cuba's patron saint], which ended in a march against the Revolution in Havana in 1961, to the visit of pope John Paul II in 1998 and the reconciliation and restructuring of the Catholic Church on the island. As a constant background concern, the chronology takes into account the dilemma between "revolution" and "Catholicism that was introduced in 1959. Thus, the essay traces the long road from initial divergence to the current climate of religious freedom and conciliatory dialogue between Church and State in Cuba.